PERAN SYSTEM QUALITY DAN INFORMATION QUALITY DALAM MENDUKUNG KEBERHASILAN IMPLEMENTASI SIMDA DESA (STUDI KASUS PADA DESA-DESA DI KABUPATEN BANGKA) - Abu Nizarudin (JURNAL RISET TERAPAN AKUNTANSI, 2018)
This study aims to analyze the effect of system quality and information quality on the success of implementation of SIMDA Desa.This study is quantitative research conducted on the Villages in Bangka. sampling technique used was purposive sampling with a sample of 24 respondents. Data analysis technique used is quantitative analysis.The results showed that the system quality and information quality either partially or simultaneously has a positive and significant impact on the success of the implementation of SIMDA Desa.